Introduction to cuban space physiology meeting and gravity of exercise for a mission to Mars - Hargens, Alan; Petersen, Lonnie G (Revista Cubana de Investigaciones Biomédicas, 2019)
In order to develop effective countermeasures to maintain the health and well-being of crew members during prolonged spaceflight, such as a mission to Mars, an integrated physiologic view is necessary. Future spacecraft to deep space will be constrained by limited volume, food, water, shelter and other resources. Thus, it's important to understand the highest risks and to direct research into these areas. This review paper examines important risks during a 2-3 year mission to Mars with a view to provide devices and methods to integrate across many physiologic systems in an attempt to reproduce activities of daily living on Earth. Because effective hardware for artificial gravity by centrifugation may be decades away, we propose use of lower body negative pressure (LBNP) as means to simulate multiple beneficial effects of gravitational stress including blood and fluid shifts towards the feet and mechanical loading of the body. LBNP-devices are reconfigurable as wearable suits to reduce mass or combined with exercise devices to increase efficacy of exercise in weightlessness.